Effects of construction waste powder on micro–macro properties of green high-strength cement paste with low water-to-binder ratio. (3rd July 2023) - Wu, Huixia; Yang, Dingyi; Wang, Changqing; Ma, Zhiming
Highlights: Utilizing construction waste powder as binder for green high-strength paste with low w/b ratio. Investigating the properties of high-strength paste with various construction waste powders. Suggesting the utilization of construction waste powder in high-strength cement-based materials. Abstract: The replacement of cement with ground construction waste powder is considered a sustainable strategy for the production of high-strength cement-based materials. This study investigated the influences of construction waste powder types and replacements on the micro–macro characterizations of green high-strength cement paste with low water-to-binder (w/b) ratio. The results highlighted that paste with 0.2 w/b ratio contained abundant hydration products and un-hydrated cement, and construction waste powder exerted good nucleation sites and filling effects in paste. The mix of construction waste powder did not change the hydration product types but reduced calcium hydroxide content in paste. Mixing appropriate ground brick powder up to 50% declined paste drying shrinkage, but the paste drying shrinkage continuously increased as ground paste/mortar/concrete powder content increases. The maximum drying shrinkage of paste with 50% ground brick powder and 50% ground concrete powder was 3.3% lower and 32.4% higher than the plain paste. When ground brick powder content was below 50% or ground paste/mortar/concrete powder content was below 30%, construction waste powder blended paste had similar or better compressive strength than plain paste, but incorporating 70% construction waste powder reduced the paste compressive strength. When construction waste powder content was identical, ground brick powder blended paste had higher compressive strength than paste containing ground paste/mortar/concrete powder. Incorporating appropriate dosage of ground brick powder reduced the transport properties and total porosity of paste, whereas the transport properties and total porosity both increased with ground paste/mortar/concrete powder incorporation. Optimizing construction waste powder types and contents can prepare green paste owning high-strength and low transport properties.